Arachidonic Acid–Induced Dilation in Human Coronary Arterioles: Convergence of Signaling Mechanisms on Endothelial TRPV4‐Mediated Ca2+ Entry. Issue 3 (25th April 2013) - Zheng, Xiaodong; Zinkevich, Natalya S.; Gebremedhin, Debebe; Gauthier, Kathryn M.; Nishijima, Yoshinori; Fang, Juan; Wilcox, David A.; Campbell, William B.; Gutterman, David D.; Zhang, David X.
Abstract : Background: Arachidonic acid (AA) and/or its enzymatic metabolites are important lipid mediators contributing to endothelium‐derived hyperpolarizing factor (EDHF)–mediated dilation in multiple vascular beds, including human coronary arterioles (HCAs). However, the mechanisms of action of these lipid mediators in endothelial cells (ECs) remain incompletely defined. In this study, we investigated the role of the transient receptor potential vanilloid 4 (TRPV4) channel in AA‐induced endothelial Ca 2+ response and dilation of HCAs. Methods and Results: AA induced concentration‐dependent dilation in isolated HCAs. The dilation was largely abolished by the TRPV4 antagonist RN‐1734 and by inhibition of endothelial Ca 2+ ‐activated K + channels. In native and TRPV4‐overexpressing human coronary artery ECs (HCAECs), AA increased intracellular Ca 2+ concentration ([Ca 2+ ]i ), which was mediated by TRPV4‐dependent Ca 2+ entry. The AA‐induced [Ca 2+ ]i increase was inhibited by cytochrome P450 (CYP) inhibitors. Surprisingly, the CYP metabolites of AA, epoxyeicosatrienoic acids (EETs), were much less potent activators of TRPV4, and CYP inhibitors did not affect EET production in HCAECs. Apart from its effect on [Ca 2+ ]i, AA induced endothelial hyperpolarization, and this effect was required for Ca 2+ entry through TRPV4. AA‐induced and TRPV4‐mediated Ca 2+ entry was also inhibited by the protein kinase A inhibitor PKI. TRPV4 exhibited a basal level of phosphorylation, which was inhibited by PKI. Patch‐clamp studies indicated that AA activated TRPV4 single‐channel currents in cell‐attached and inside‐out patches of HCAECs. Conclusions: AA dilates HCAs through a novel mechanism involving endothelial TRPV4 channel‐dependent Ca 2+ entry that requires endothelial hyperpolarization, PKA‐mediated basal phosphorylation of TRPV4, and direct activation of TRPV4 channels by AA.